THE IMPACT OF ARTICULATION ORGAN MATURITY ON SKILLS SPEAKING CHILDREN AGED 4-6 YEARS - Sulis Setiawati; Sumarti Sumarti (Universitas Indraprasta PGRI, 2020)
Abstract: The articulation organs are announced as mature physiological functions and communication of the articulated organs is approved according to the child's age development. If these organs work well then speaking exercises are also good. However, approval of the function of these organs is not maximal, it will also be agreed on the skills of a child in his speech. The focus of this research is about learning to talk to children aged 4 s.d. 6 years directed at the child's skills in reciting consonant sounds by referring to the development table of the sound production classification of A. Smith and his friends. This study involved 32 kindergarten students with a range of ages between 4 - 6 years. The method used is descriptive qualitative. Data is collected with instruments and direct information obtained from the teacher and parents. Based on the results of the study, out of 32 students, 26 students were declared organs of articulation while 6 other students were constrained in the function of organulation so that it could increase their fluency in consonant pronunciation in conversation.Key Words: articulation organ maturity, speaking skills